Neutron-induced fission cross-section measurement of 234U with monoenergetic beams in the keV and MeV range using MicroMegas detectors - Kanellakopoulos, A.; Stamatopoulos, A.; Tsinganis, A.; Kokkoris, M.; Vlastou, R.; Kalamara, A.; Lagoyannis, A.; Axiotis, M. (HNPS Advances in Nuclear Physics, 2019)
The fission cross-section of 234U was measured at incident neutron energies between 300 and 500 keV and 4 and 5 MeV with a setup based on “microbulk” MicroMegas detectors. The standard 235,238U fission cross-sections were used as reference. The neutron beams were produced via the 7Li(p,n) and the 2H(d,n) reactions at the neutron beam facility of the 5.5 MeV Tandem accelerator laboratory at NCSR “Demokritos”. The mass of the actinide content of the targets used and of their impurities was quantitatively determined via α – spectroscopy. The developed methodology and preliminary results are presented.